The Complete Plays of Jean Racine : Volume 4: Athaliah - Racine, Jean, 1639-1699 (Book collections on Project MUSE., 2012)
As Voltaire famously opined, Athaliah, Racine's last play, is "perhaps the greatest masterwork of the human spirit." Its formidable antagonists, Athaliah, queen of Judah, and Jehoiada, high priest of the temple of Jerusalem, are engaged in a deadly struggle for dominion: she, fiercely determined to maintain her throne and exterminate the detested race of David; he, no less fiercely determined to overthrow this heathen queen and enthrone the orphan Joash, the scion of the house of David, whom Athaliah believes she slew as an infant ten years earlier. This boy represents the sole hope for the survival of the royal race from which is to spring the Christ. But in this play, even God is more about hate and retribution than about love and mercy. This is the fourth volume of a projected translation into English of all twelve of Jean Racine's plays-only the third time such a project has been undertaken. For this new translation, Geoffrey Alan Argent has rendered these plays in the verse form that Racine might well have used had he been English: namely, the "heroic" couplet. Argent has exploited the couplet's compressed power and flexibility to produce a work of English literature, a verse drama as gripping in English as Racine's is in French. Complementing the translation are the illuminating Discussion, intended as much to provoke discussion as to provide it, and the extensive Notes and Commentary, which offer their own fresh and thought-provoking insights